Analisis Risiko Produksi Bunga Mawar Tabur di Desa Candi Kecamatan Bandungan - Jaragi, Figo Ahmad Putra; Setiyawan, Hery; Handayani, Migie (Universitas Galuh, 2025)
The production risks of rose petals posed challenges faced by farmers in maintaining the quality and quantity of flower production. This study aimed to analyze the sources of production risk, the priority risk agents, and the implementation of risk mitigation strategies. The research was conducted in October - November 2024 in Desa Candi, Bandungan District, Semarang Regency, Central Java. The research method used was a case study approach, with a census technique used for sampling. The sampling for this study involved 17 rose petal farmers in Desa Candi, Bandungan District. Primary data collection methods included observation and interviews, while secondary data included production data from each harvest period, along with literature from previous researchers. Descriptive analysis was performed using the ARP formula, while quantitative analysis applied Failure Mode and Effect Analysis (FMEA) and House of Risk (HOR) methods, phases one and two. Based on the analysis results KV poin is 0,4491, that the highest production risk was roses and stems attacked by pests and diseases, with a severity value of 5.35. The highest occurrence value was recorded for fruit and trees attacked by pests and diseases, with a value of 6.41. Five risk agents were identified as priorities: increased pests and diseases, fruit and trees attacked by pests and diseases, suboptimal pest and disease management, rose tree mortality/reduction, and extreme or unpredictable weather changes. Five risk mitigation strategies were identified, including routine spraying and increasing pesticide doses, which proved very effective in reducing pest attacks and maintaining plant quality. Farmers adopted mechanical and chemical control methods for pest management, as well as monitoring and replanting as responses to unpredictable weather conditions.